Is investigation of patients with haemoptysis and normal chest radiograph justified?. Issue 10 (19th May 2009) - Thirumaran, M; Sundar, R; Sutcliffe, I M; Currie, D C
Abstract : Background: Haemoptysis is a common clinical symptom. A small proportion of patients present with haemoptysis and normal chest radiograph. The investigation strategy for this group of patients is unclear. The aim of this study is to see whether further investigations for this group of patients are justified. Methods: A retrospective analysis was conducted of consecutive patients presenting with haemoptysis and normal chest radiograph over a period of 56 months irrespective of their smoking status. These patients were investigated by CT of the thorax and fibreoptic bronchoscopy. Results: 275 episodes of haemoptysis with normal chest radiograph were investigated further in 270 patients (60% males). The median age was 60 years. Twenty-six patients were diagnosed to have respiratory tract malignancies (larynx, 1; trachea, 1; lung, 22; carcinoid, 1; and leiomyoma, 1). Eight (31%) of the 26 patients with respiratory tract malignancy had radical treatment. Fibreoptic bronchoscopy was diagnostic of cancer in 14 (54%) of the 26 patients with malignancy. CT of the thorax was suggestive of cancer in 24 (96%) of the 25 patients with malignancy. Conclusion: It is concluded that further investigation of haemoptysis in smokers is justified regardless of the amount or frequency of haemoptysis based on a 9.6% rate of malignancy in this consecutive series. It is recommended that these patients are investigated with CT of the thorax followed by fibreoptic bronchoscopy.